2002
DOI: 10.1038/sj.bmt.1703515
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in vivo purging is safe and effective in combination with CD34-positive selected autologous stem cell transplantation for salvage therapy in B-NHL

Abstract: Summary:The purpose of this study was to evaluate feasibility and efficacy of Rituximab included into a sequential salvage protocol for CD20 + B-NHL in relapse or induction failure. Twenty-seven patients with CD20 + B-NHL in relapse or induction failure received Rituximab combined with DexaBEAM (R-DexaBEAM) for stem cell mobilization. Additional ex vivo selection of CD34-positive cells was performed using the CliniMacs device. Two doses of Rituximab were included in the high-dose therapy regimen (HDT). R-Dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
1
39
1
1
Order By: Relevance
“…33 This finding may reflect B-cell depletion and resulting hypogammaglobulinemia in these patients. Transient pancytopenia, another cause for the increase in infections, occurred in 6 of 23 patients treated with rituximab after transplant.…”
Section: Original Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…33 This finding may reflect B-cell depletion and resulting hypogammaglobulinemia in these patients. Transient pancytopenia, another cause for the increase in infections, occurred in 6 of 23 patients treated with rituximab after transplant.…”
Section: Original Approachmentioning
confidence: 97%
“…Studies using rituximab in the peri-transplant period are summarized in Table 4. Flohr et al 33 conducted a study to evaluate the safety and effectiveness of rituximab in combination with DexaBEAM as mobilization therapy in 27 B-cell lymphoma patients. They showed significant depletion of peripheral B cells without engraftment delays.…”
Section: Original Approachmentioning
confidence: 99%
“…7 Regimens, such as high-dose cytosine arabinoside, 8,9 HAM (high-dose cytosine arabinoside/ mitoxantrone), 10 and DexaBEAM (dexamethasone/ BCNU/etoposide/cytosine arabinoside/melphalan), 11 have been used in conjunction with rituximab during mobilization procedures, to obtain tumor-free progenitor cells. Although sufficient numbers of PBSC could be obtained using these regimens, the timing of leukapheresis differed with each case, because decisions were based on measurement of CD34 þ cells or platelet recovery in the PB.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of trials utilizing rituximab as in vivo purging prior to ASCT have suggested high molecular response rates. [34][35][36][37] Long-term follow-up of these studies is required to establish PCR as a reliable surrogate marker of clinical response in this situation.…”
Section: Discussionmentioning
confidence: 99%